2022
DOI: 10.1155/2022/5871188
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of WDHD1 in the Occurrence of Esophageal Cancer as a Downstream Target of PI3K/AKT Pathway

Abstract: Esophageal cancer is one of the most common malignant tumors in the world, which is characterized by high incidence, strong invasiveness, high mortality, and poor prognosis. At present, the therapies include surgery, endoscopic resection, radiotherapy and chemotherapy, targeted therapy, and immunotherapy. The five-year survival rate of esophageal cancer has not been significantly improved, although the medical level has been continuously improved and the management and application of different therapies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
3
3
0
Order By: Relevance
“…Their subsequent cell experiment illustrated that WDHD1 acted as a pivotal cell cycle regulator and an essential component of the phosphoinositide-3-kinase-protein kinase B (PI3K)/Akt pathway. Similar conclusions were reached by Xian et al who suggested that WDHD1 might be an irreplaceable tumor factor in the case of esophageal cancer [ 18 , 69 ]. Concerning CHOL, inhibiting WDHD1 repressed cell migration and invasion while promoting cell apoptosis [ 63 ].…”
Section: Discussionsupporting
confidence: 84%
“…Their subsequent cell experiment illustrated that WDHD1 acted as a pivotal cell cycle regulator and an essential component of the phosphoinositide-3-kinase-protein kinase B (PI3K)/Akt pathway. Similar conclusions were reached by Xian et al who suggested that WDHD1 might be an irreplaceable tumor factor in the case of esophageal cancer [ 18 , 69 ]. Concerning CHOL, inhibiting WDHD1 repressed cell migration and invasion while promoting cell apoptosis [ 63 ].…”
Section: Discussionsupporting
confidence: 84%
“…In the study, they performed experiments involving immunoprecipitation of labeled WDHD1 and recombinant AKT1 protein as a kinase. Results showed that AKT1 directly phosphorylated WDHD1 as determined by the kinase analysis using PAS antibody immunoblotting [80]. These findings present convincing evidence that WDHD1 functions as a downstream target of the PI3K/AKT pathway (Figure 5).…”
Section: Pi3k/akt Pathwaysupporting
confidence: 64%
“…As the downstream target of the PI3K/AKT pathway The occurrence and survival of tumors [80] As a cell cycle regulator and a downstream molecule in the PI3K/AKT pathway The occurrence and survival of tumors [19] Weighted gene co-expression network analysis As a hub gene [81] Lung adenocarcinoma…”
Section: Nasopharyngeal Carcinoma Regulating Itgav Expression Affect ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we reviewed senescence and apoptosis pathways and found that PIK3CA was a gene that co-regulated senescence and apoptosis pathways. PIK3CA encodes the p110a catalytic subunit of PI3K, which is responsible for the transformation of PI(4,5)P2 to the second messenger PI(3,4,5)P3, thus activating the PI3K signaling pathway and triggering a series of intracellular signal transmission, including cell cycle, apoptosis, P53 pathway, etc [31][32][33]. P53 is an important factor in the downstream of PI3K signaling pathway.…”
Section: Discussionmentioning
confidence: 99%